Influence of RRA treatment on microstructure and stress corrosion cracking behavior of spray formed 7075 alloy - Rui-Ming Su; Ying-Dong Qu; Rong-De Li; Jun-Hua You (Фізико-хімічна механіка матеріалів, 2015)
The effects of retrogression via under pre-aging on microstructure, mechanical properties and stress corrosion cracking behavior of spray formed 7075 aluminum alloy were investigated by transmission electron microscope, tensile test and slow strain rate test. The results show that with under aging at 120°C for 16 h as pre-aging, the strength of the alloy can maintain at a high level and grain boundary precipitates are discrete after retrogression and re-aging treatment. However, retrogression treatment is uncontrollable by shortened retrogression period. After retrogression at 200°C for 8 min and re-aging, the ultimate tensile strength, elongation and SCC index of the alloy is 791 MPa, 8.5% and 0.155 respectively.